Implementation of TVUPI'S VCDLN Super-App for Teachers - Darmawan, Deni; Wahyudin, Dinn; Suherman, Yuyus; Risda, Dianni (Universitas Pendidikan Indonesia (UPI), 2023)
This research aims to evaluate a research product in the form of TVUPI'S VCDLN Ecosystem Multiplatform Super-App Based on Artificial Intelligence (AI), which was developed using the ADDIE Method. The research results obtained need analysis data from 18 Districts in Indonesia. The Design and Development stages are carried out based on seven frameworks from AI. At the product implementation stage, educators from South Korea, Japan, and Indonesia produced: (1) Deep learning with scores of 142, 135, 142; (2) NLP with a score of 133, 145, 140; (3) Robotic with a score of 145,148, 130, and (4) Experts system with a score of 135,135,140. From the results of analysis and experts from Bordeaux University, it is recommended that Deep Learning and Robotics frameworks are of great interest to educators. In conclusion, research products can be used in Indonesia and Asia.